(untitled) (Research, Society and Development, 2022)
Sedentary behaviors (SB) may be associated with components of the metabolic syndrome (MS) in quilombolas. The aim of this study is to investigate the association between SB, sitting time and TV time, with the components of MS. This is an epidemiological, cross-sectional, population-based study with quilombolas living in the microregion of Guanambi, Brazil. Data were obtained through interviews, anthropometric measurements, blood pressure measurements and blood collection. Analyzes were performed: descriptive; One-way ANOVA; MANOVA; Principal Component Analysis (PCA); and comparison by BoxPlot. The results indicate that, among the 850 quilombolas, the following prevailed: female (61.2%); with lower income (79%); and with TV time ≥5h (69.7%). In PCA, the components of MS were not associated with SB. However, the ANOVA showed that the time spent on TV, among the elderly, was associated (p<0.05) with waist circumference (WC), with a difference between the times of four hours and ≥5 hours. It is concluded that there was no association between SB and MS components. However, in elderly quilombolas, WC can be an indication of health applicable in the monitoring and prevention of MS.